2021
DOI: 10.3390/toxics9030065
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons Contamination of Flamed and Braised Chickens and Health Risk Assessment in Burkina Faso

Abstract: Charcoal- or wood-cooked chicken is a street-vended food in Burkina Faso. In this study, 15 samples of flamed chicken and 13 samples of braised chicken were analyzed for 15 priority polycyclic aromatic hydrocarbons (PAHs) with a high-performance liquid chromatography-fluorescence detector. A face-to-face survey was conducted to assess the consumption profiles of 300 men and 300 women. The health risk was assessed based on the margin of exposure (MOE) principle. BaP (14.95–1.75 μg/kg) and 4PAHs (BaP + Chr + BaA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Barro et al (2002) [21] Kagambega et al (2012) [22] and Somda et al (2018) [23] PLOS ONE reported the presence of pathogens in processed meats sold on the street in Burkina Faso. It has been reported a chemical risk assessment of metallic trace elements and polycyclic aromatic hydrocarbons [24,25] associated with the consumption of flamed and braised chicken in Burkina Faso. However, very little information is available on the presence of HAAs in processed chicken in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%
“…Barro et al (2002) [21] Kagambega et al (2012) [22] and Somda et al (2018) [23] PLOS ONE reported the presence of pathogens in processed meats sold on the street in Burkina Faso. It has been reported a chemical risk assessment of metallic trace elements and polycyclic aromatic hydrocarbons [24,25] associated with the consumption of flamed and braised chicken in Burkina Faso. However, very little information is available on the presence of HAAs in processed chicken in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%